The Effect of Ni/AC and Mo/AC Catalyst Arrangements on the Activity and Selectivity for Hydrotreating Palm Cooking Oil into Biojet Fuel - Trisunaryanti, Wega; Wijaya, Karna; Saputro, Muhammad Darul Ikhsan (Indonesian Journal of Chemistry, 2025)
This research was done to study the effect of the arrangement of nickel (Ni) and molybdenum (Mo) metals impregnated with activated carbon on the activity and selectivity of the hydrodeoxygenation (HDO) of palm cooking oil into biojet fuel. The catalysts were synthesized by impregnating Ni and Mo metals by dry spray impregnation method with precursor salts nickel(II) nitrate hexahydrate (Ni(NO3)2·6H2O) and ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O24·4H2O) solutions, respectively on the activated carbon. The catalysts were characterized using FTIR, XRD, SAA, SEM-EDX, and NH3-TPD instruments. The catalyst performance was tested using a semi-batch reactor with dual heaters in a one-pot system, atmospheric pressure, and a hydrogen gas flow rate of 20 mL min−1 for the palm cooking oil HDO reaction for 3 h. The obtained liquid products were analyzed using gas chromatography-mass spectrometry (GC-MS). The best catalyst arrangement was the Ni/AC catalyst in a double-layer arrangement, which had 6.25 wt.% metal content, and a surface area of 803.89 m2 g−1 which resulted in 24.75 wt.% yield with 86.93% (fraction 1) and 87.48% (fraction 2) selectivity. This research concluded that catalyst layer arrangement affects the catalytic activity and selectivity in the HDO of palm cooking oil.